Surface Roughness Values of Magnesium Alloy AZ31 When Turning by Using Rotary Cutting Tool - Gusri Akhyar; Suryadiwansa Harun; Arinal Hamni (Universitas Lampung, 2016)
Abstract - Magnesium and magnesium alloys is one of materials that worldwide used on automotive components due to very good strength to weight ratio, resistant to corrosion, lighter compare to steel materials. Other than that magnesium has an advantage in easy to form and good machinability. Nevertheless, magnesium known as metal which is easy to burned because of magnesium has low melting point. To maintain magnesium from burning quickly when proses machining, it needs to use coolant or lubricant to reduce temperature. Using of coolant when machining process can reduce temperature on cutting tool and work piece material, while using of lubricant can reduce friction between the cutting tool and work piece mateial. However, using of coolant and lubricant can harm for the environment and also coolant difficult to destroyed. Therefore, an alternative method to reduce the temperature when machining of magnesium alloy is using the rotary cutting tool system. In the rotary cutting tool system, the cutting tool has a time to experience cooling in the period time. Other than aspect of temperature, surface roughness values are representative of surface of quality of produced componens. In this research, surface roughness value of magnesium alloy of AZ31 observed in ranges of work piece cutting speed of (Vw) 25, 50, 120, 160, 200 m/min, rotary cutting speed of (Vt) 25, 50, 75 m/min, feed rate of (f) 0,05 and 0,10 mm/rev, and depth of cut of 0.2 mm. The turning process was done by using two kinds of diameter of rotary cutting tools are 16 and 20 mm, and without applying of coolant. The results of the research showed that the minimum surface roughness value of machined surface was 0,62????m by using insert with diameter of 16 mm, while the maximum surface roughness value of machined surface was 2,86 ????m by using insert with diameter of 20 mm. This result stated that the increase in the diameter of rotary cutting tool gives a significant effect on the produced surface roughness value. Factor of feed rate also gives a significant contribution on the surface roughness value of machined magnesium surface. The increase in feed rate generated significantly surface roughness value as long as the trials experiments. The produced surface roughness values inversely proportional to the cutting speed of rotary cutting tool.Keywords - magnesium, rotary tool, surface roughness, turning.